THE STRENGTHENING CHARACTER EDUCATION PERSPECTIVE OF KI HAJAR DEWANTARA AND THE MINISTRY OF EDUCATION AND CULTURE - Sidon, Bey Arifin; Hidayah, Fathi; Muria, Muhammad Sholeh (INCARE, International Journal of Educational Resources, 2023)
This study aims to combine and analyze between the two in terms of educational character. This research is a literature research or library research. Data collection was carried out by exploring literature, both primary and secondary which discussed character education, the data was collected then made a summary to determine more specific boundaries about the object of study from the books. The data analysis technique used is descriptive analysis. Character education (PPK) from the perspective of Ki Hajar Dewantara from the aspect of habituation includes: 1) discipline; 2) hard work; 3) independent; 4) social care, and; 5) responsibility. Meanwhile, the exemplary aspect includes: 1) love for the motherland; 2) friendly/communicative, and; 3) social care. Strengthening character education from the perspective of the Ministry of Education and Culture in the aspect of habituation includes: 1) religious; 2) honest; 3) discipline; 4) friendly/communicative; 5) care for the environment, and; 6) social care. Meanwhile, the exemplary aspect includes: 1) independent; 2) friendly/communicative, and; 3) national spirit. The KDP similarities between the two perspectives lie in the similarities in the characters developed. While the difference lies in two things, namely: 1) differences in reinforcement for different characters, and 2) differences in how reinforcement for the same character.